Cryptocurrencies and the Contractual Freedom in International Private Law and in the Brazilian Legal System - Dall Agnol Pinto, Tamara Luiza; Catão, Adrualdo de Lima (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
This article deals with the use of cryptocurrencies and their respective technological structure within the international community and in Brazil. It is known that law is a dynamic social science, insofar as it must adapt to realities. Today it is impossible to ignore the growing transactions of equity content that take place through virtual currency, which differs from electronic currency. Adopting the liberal theoretical framework, the legitimacy and viability of cryptocurrencies will be demonstrated as a bargaining chip, focusing the study on the core of international and national contracts, verifying the support (or not) of domestic private law, and how they may prove to be solutions to major problems, despite the progressive eagerness of States to regulate them in order to avoid decreases in their revenue. Methodologically, the literature review is used, as well as the analysis of regulations, jurisprudence and media reports.